Mapping Analysis of Active Fire Protection System on Dormitory Building in X University - Eka Rosanti; Selamet Ujang Irawan; Rindang Diannita; Muhammad Rifki Taufik (Universitas Airlangga, 2021)
Introduction: Fire cases increase in residential buildings because short circuits, at dormitories are mostly affected by human factors. X university dormitory building is a place for 24 hours of students’ activities with a lot of electricity consumption, bad behavior; overpowering extensions, and many flammable objects such as paper and furniture. Research objectives are to investigate the appropriateness and mapping needs of fire protection systems with regulations. Methods: The research is a semi quantitative analysis. Primary data is conducted with observations by using a checklist form that refers to the regulations and results of managers' interviews. The obtained data are categorized into good with suitability >79-100%, moderate ≥60%-79% and poor <60%. Result: The appropriateness of the active fire protection system is under 60% or in the poor category. The appropriateness of the fire extinguisher is 47.77%, the hydrant is 58.75%, the alarm is 18.75% and the heat detector is 35.90%. There is no sprinkler installation in the dormitory building and no commitment from the top management regarding occupational safety and health. Fire extinguisher’s need is 10 tubes per floor, the number of hydrants have been fulfilled, alarm requires an additional 1 unit on each floor and a heat detector requires a total of 114 units. Conclusion: The active fire protection system is still under 60% (poor category) and no maintenances. Based on the aforementioned mapping results, it needs to add the number of piece equipment according to the regulations and maintenance efforts.Keywords: active fire protection system, dormitory, mapping